Anchoring mechanical characteristics of Ductile-Expansion bolt - Yu Chen; Wang Liu; Linchong Huang; Hang Lin; Yixian Wang; Yanlin Zhao; Cungang Lin (International Journal of Mining Science and Technology)
The application of ductile rock bolts has been a crucial method for solving the problems of large deformations, energy absorption and stability control issues in deep rock masses. To study the anchoring mechanism of the key expansive structure, this paper proposes a novel type of bolt — the Ductile-Expansion bolt, and conducts research on anchoring mechanics, energy absorption characteristics, and failure modes of the bolt. In addition, this paper defines the concept of load-volume ratio of metal rock bolts and proves the Ductile-Expansion bolt is capable of better improving the unit volume bearing capacity of the bolt material. Furthermore, laboratory and field tests verify the Ductile-Expansion bolt had better anchoring effect than the traditional rebar bolt, with the expansion structure favorably enhancing the ductility and energy absorption performance of the bolt. Finally, this paper microscopically analyzes the crack propagation and distribution morphology of the bolts by establishing a 3D coupled numerical model based on FDM-DEM. Numerical results illustrate the interface at the variable diameter of the Ductile-Expansion bolt serves as the transition zone between high and low stress levels. The expansion structure can impose radial compression on the medium around the bolt, which can improve the bolt anchorage performance.